The impact of work ethics in improving marketing performance (Field study in private banks in Lattakia Governorate) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study mainly aimed at determining the impact of work ethics in its dimensions (honesty and integrity, integrity and transparency, independence and objectivity) on improving the marketing performance of private banks in Lattakia Governorate.  The researcher followed the analytical descriptive approach, and a set of methods, including relying on secondary and primary data, through a questionnaire designed and distributed to (120) respondents, from which (115) were retrieved, and (99) questionnaires were valid for analysis, and the research community consisted of a cadre of workers in Private banks in Lattakia Governorate, then the SPSS program was relied upon as a tool for analyzing the available data.The study concluded that there is a significant impact of work ethics in improving the marketing performance of private banks in Lattakia, and the worker does not avoid any relationships that may appear to lose objectivity and independence when doing business, and the bank does not continuously seek to maintain and expand its market share, and the bank does not seek to increase its sales from in its marketing strategies.